Optimization parameters for Mycobacteria confluentis biodegradation of PAHs - Ibrahim, Muna; Makky, Essam A.; Nina Suhaity, Azmi; Jamil, Ismail (EDP Sciences, 2018)
In this study, the effect of process parameters (incubation period, temperature, initial pH-value, concentration of PAHs in the medium, and bacterial inoculum size) on the biodegradation of PAHs using Mycobacteria confluentis was studied using One-Factor-At-a-Time (OFAT) method. From the results of the study, it was observed that the studied parameters had significant effects on the degradation process. The capability of Mycobacteria confluentis on the degradation of PAHs was found to be maximum when the initial pH of the PAH was 7, temperature 40 °, PAH concentration of 50 μL, bacterial concentration of 7.5 mL, and incubated for 3 to 5 days. This condition gave a PAH degradation percentage of 40 to 50 %, showing a similarity to most previous studies where the maximum percentage of degradation has been around 40 to 50 %. This study, therefore, concludes that Mycobacteria confluentis is a good PAHs degrader which can be of significant important in the management of oil polluted fields and environments.